GREEN SUPPLY CHAIN MANAGEMENT AND SAMPLE APPLICATIONS - Beste DESTİCİOĞLU (National Defense University Barbaros Naval Sciences and Engineering Institute Journal of Naval Science and Engineering, 2021)
It has become inevitable to develop new distribution strategies with the depletion of natural resources, global warming, increased environmental pollution due to the increasing competition conditions in recent years. In addition, the concepts of green supply chain and green logistics come into effect the literature with the awareness of both non-governmental organizations and national and international administrations about this danger. Green supply chain includes all activities, carried out in the design process of the product, the selection of the machinery, raw materials and semi-finished products used in the manufacture of the product to the retailer and/or the end customer, and the recycling of the product from the customer after the economic life and function is completed, and recycling. In this study, firstly, the emergence of green supply chain management and green logistics concepts are discussed within the literature review, taking into account the current developments. Later, green supply chain management and new concepts that emerged with this approach were discussed. In the continuation of the study, examplary green supply chain studies in Turkey were mentioned and suggestions were made to guide companies that will implement this approach.